Pengaruh Intensif, Tingkat Pendidikan, Pelatihan Dan Pengalaman Kerja Pada Kinerja Individu Pengguna Sistem Informasi Akuntansi - Belawa, Putu Dhana; Pande Dwiana Putra, I Made (E-Jurnal Akuntansi; Vol 22 No 1 (2018), 2018)
Denpasar Industry and Trade Office in supporting and carrying out its activities requires adequate individual performance related to the use of accounting information system. This  study aimed to determine the effect of incentives, level of education, training and work experience on the performance of individual user of acccounting information system unit in industry and trade office Denpasar city . This study was conducted at Denpasar Industry and Trade Office in 2017 by making all employees of accounting information system users who work at Disperindag Denpasar City as many as 60 employees as a sample with census method. The data were collected by interviewing, distributing questionnaires, and analysis techniques using multiple linear regression. Based on the results of the analysis, it is known that intensive, level of education s , training and work experience positively affect the individual performance of accounting information system users in industry and trade ofice of Denpasar City .   Keywords :  icentives, level of educations, training, work experience, performance of individual user of accounting informations system